THU0386 Seven Cases of Multicentric Reticulohistiocytosis Treated with Intravenous Administration of Alendronate. (10th June 2014) - Hamamoto, K.; Goto, H.; Yamada, S.; Yoda, M.; Yoda, K.; Imanishi, Y.; Inaba, M.
Abstract : Background: Multicentric reticulohistiocytosis (MR) is a rare systemic disorder characterized by cutaneous papulonodular lesions and severe destructive arthritis. Histologic analysis of cutaneous and synovial lesions discloses infiltration by multinucleated foreign body-type giant cells and smaller histiocytes. There is no consistently effective therapy for MR. It was reported that aminobisphosphonates such as alendronate act directly on macrophages by inhibiting the mevalonate pathway and that bisphosphonates have anti-inflammatory and anti-arthritic effects in animal models of arthritis. For these reason we tried to treat MR with aminobisphosphonates and reported the first case of successful treatment of MR with intravenous administration of alendronate in 2003. Objectives: To verify efficacy of alendronate for MR, seven MR patients (1 male and 7 females, mean age of 55.1 (30-75) years) were treated with alendronate intravenously. Methods: Alendronate was given intravenously 10 mg once a month for one year to each patient. Other drugs previously started were continued. Results: Skin manifestation and arthritis were markedly improved in all seven cases. Three cases stayed in remission status after treatment completed. Two cases stayed in remission however continuation of maintenance administration of alendronate was necessary. One severe case showed improvement of existing skin lesion and arthritis, but developed new skin and mucomembranous lesion. One male case showed flare-up one year after completion of treatment but improved again after resection of newly diagnosed epididymis tumor. Except for transient fever in two cases, alendronate has not caused any other adverse event including bisphosphonate-related osteonecrosis of the jaw. In all cases joint pain and activity of daily living was markedly improved, however bone erosions were not improved. Conclusions: Alendronate may be the first line drug for MR treatment that may produce a remission, and may be safer than conventional treatment such as immunosuppressant, more over can be used with any other treatment. References: Arthr Rheum 2003 48: 3538-41. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.5879